Clinical – Immunological Characteristics Urogenital Candidiosis in Pations with Pulmonary Tuberculosis - Tursunova Feruza; Saipova Nodira (Genius Journals, 2023)
Candidal lesions of the mucous membrane of the genital organs - Urogenital candidiosis (UGK) — wide widespread disease in women of reproductive age. Its share in the structure of infectious pathology of the lower parts urogenital systems is from 24 to 45%. Approximately 75% of women experience at least one episode of vulvovaginal candidiasis during their lifetime, 40-45% have two or more episodes , 10-20% develop a complicated process, requiring long treatment [1-4]. In recent decades, candida infection has been considered How disease contemporary civilization, "disease from treatment", being reflection of dynamic changes etiological structures infectious pathology on background urbanization of society, widespread uncontrolled use of drugs funds, environmental stress and social problems that have a negative impact on human health. The very fact of the disease, itch, discomfort, pain cause at patient current psychological stress, feeling self-doubt, significantly reducing the quality of life.
Keywords: Urogenital candidiasis; pulmonary tuberculosis; immunogram